Administrative Employees’ Job Satisfaction in Selected Campuses of (TU) in Kathmandu Valley: An Empirical Study (Voice of Teacher, 2021)
Job satisfaction is a positive feeling of employees toward their job because unsatisfied employees are quite their job. Satisfied employees are less absent, contribute to the benefit of an organization and stay in the organization. Only happy employees should enhance organizational efficiency and performance. It is a combination of psychological, physiological and environmental circumstance which derives to the person; I am satisfied with my job. It is accepted that individual differences in employee job satisfaction can be measured and managed by an organization. This study was organized to identify the variables influencing job satisfaction of administrative staffs, so the samples were taken from randomly selected campuses, TU in Kathmandu Valley.Primary data were collected from distribution 148 structured questionnaires with six points Likert scale developed in the Job description index (JDI). Only 106 respondents’ opinions were analyzed by the bits of the help of descriptive and inferential statistical tools. The finding showed that satisfied variables are co-workers, supervisors and promotion. The satisfaction level of gender has not found different but different according to age groups.